2020
DOI: 10.1159/000507179
|View full text |Cite
|
Sign up to set email alerts
|

In-Hospital Outcomes and Trends of Tricuspid Valve Surgery in Heart Transplant Patients

Abstract: Introduction: Tricuspid valve (TV) regurgitation is the most common valvular pathology after orthotopic heart transplant (OHT). The number of transplants being performed is increasing with patients living longer after heart transplant. Data on TV surgery in OHT recipients is limited. Methods: We sought to analyze the outcomes of patients undergoing TV surgery from a large diverse, multicentric, nationwide cohort using the Nationwide Inpatient Sample (NIS) database. Results: A total of 42,766 TV repair or repla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Severe TR inevitably leads to RV dilatation combined with a potential overestimation of RV function. However, RV function is an important determinant of the most common postoperative complications in OHT patients (cardiogenic shock and acute kidney injury) ( 2 ). Both our patients had dilated RVs with seemingly normal function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Severe TR inevitably leads to RV dilatation combined with a potential overestimation of RV function. However, RV function is an important determinant of the most common postoperative complications in OHT patients (cardiogenic shock and acute kidney injury) ( 2 ). Both our patients had dilated RVs with seemingly normal function.…”
Section: Discussionmentioning
confidence: 99%
“…Severe TR is associated with increased morbidity and mortality. However, tricuspid valve (TV) surgery in OHT patients is also associated with high perioperative risk, and therefore, alternative treatment options are warranted ( 2 ). We present 2 cases of elderly OHT patients with severe TR who underwent percutaneous treatment.…”
mentioning
confidence: 99%
“…3 Although successful surgical repair or replacement can lead to significant improvement in heart failure, tricuspid surgery after heart transplant is associated with high morbidity and mortality. 12 The experience in percutaneous tricuspid valve repair has been accumulating. A recent multicenter observational study reported 97% procedural success rate of percutaneous tricuspid valve repair using MitraClip system as well as improvement in heart failure symptoms in non-surgical candidates with severe tricuspid regurgitation.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical corrections by either repair or replacement have been the mainstay of the treatment for diuretic‐refractory cases 3 . Although successful surgical repair or replacement can lead to significant improvement in heart failure, tricuspid surgery after heart transplant is associated with high morbidity and mortality 12 …”
Section: Discussionmentioning
confidence: 99%
“…1 However, tricuspid surgery in HT patients is associated with a number of complications. 2 Thus, severe TR, which is often associated with right heart failure symptoms and increased mortality, remains a major unsolved problem in many HT patients.…”
mentioning
confidence: 99%